The 1st EMBO workshop on PVC bacteria - Planctomycetes - Verrucomicrobia - Chlamydiae superphylum: exceptions to the bacterial definition? - Devos, Damien; Jogler, Christian; Fuerst, John A. (Antonie van Leeuwenhoek, 2013)
The PVC superphylum is a phylogenetically supported collection of various related bacterial phyla that comprise unusual characteristics and traits. The ‘PVC’ abbreviation derives from Planctomycetes, Verrucomicrobia and Chlamydiae as members of this superphylum, while additional bacterial phyla are related. There has recently been increasing and exciting interest in the cell biology, physiology and ecology of members of this superphylum, including evolutionary implications of the complex cell organization of some species. It is timely that international researchers in the PVC superphylum field met to discuss these developments. The first meeting entirely dedicated to those bacteria, the EMBO workshop “PVC superphylum: Exceptions to the bacterial definition” was held at the Heidelberg University to catalyze the formation of a vital scientific community supporting PVC-bacterial research. More than 45 investigators from more than 20 countries (PIs, senior scientists and students) attended the meeting and produced a great starting point for future collaborative research. This Special Issue will focus on the EMBO-PVC meeting. This Perspective briefly summarizes the history of PVC-research, focusing on the key findings and provides a brief summary of the meeting with a focus on the major questions that arose during discussion and that might influence the research in the years to come.